2017
DOI: 10.1007/s40167-017-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of encoding instructions and response bias on cross-cultural differences in specific recognition

Abstract: Prior cross-cultural research has reported cultural variations in memory. One study revealed that Americans remembered images with more perceptual detail than East Asians (Millar et al. in Cult Brain 1(2–4):138–157, 2013). However, in a later study, this expected pattern was not replicated, possibly due to differences in encoding instructions (Paige et al. in Cortex 91:250–261, 2017). The present study sought to examine when cultural variation in memory-related decisions occur and the role of instructions. Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, these two theories posit that either activation processes occurring during encoding or both gist and verbatim traces that are formed during encoding do not work in isolation and instead interact with additional control and decision processes that generally occur during memory retrieval, for instance criterion-setting or response bias (Benjamin, 2007;Curran, Debuse, & Leynes, 2007;Kapucu, Rotello, Ready, & Seidl, 2008;Paige, Amado, & Gutchess, 2017;Verde & Rotello, 2007). Considering the cost of errors under competitive contexts, participants may show a shift towards conservatism in decision strategy as the optimal decision criterion to minimize the likelihood of false recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these two theories posit that either activation processes occurring during encoding or both gist and verbatim traces that are formed during encoding do not work in isolation and instead interact with additional control and decision processes that generally occur during memory retrieval, for instance criterion-setting or response bias (Benjamin, 2007;Curran, Debuse, & Leynes, 2007;Kapucu, Rotello, Ready, & Seidl, 2008;Paige, Amado, & Gutchess, 2017;Verde & Rotello, 2007). Considering the cost of errors under competitive contexts, participants may show a shift towards conservatism in decision strategy as the optimal decision criterion to minimize the likelihood of false recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Another study (Paige, Amado et al, 2017) found cul-tural differences in response bias rather than in sensitivity. The present study finds differences in measures of both sensitivity and response bias, helping to connect prior studies that emphasized one or the other (e.g., Millar et al, 2013;Paige, Amado et al, 2017). This evidence for response bias differences supports our ultimate conclusion which is that mechanisms besides pattern separation contribute to cross-cultural differences in memory specificity.…”
Section: Discussionmentioning
confidence: 94%
“…The ‘approach/avoid/stay’ trial prompts were intended to ensure participants paid attention and encoded items throughout the experiment, as the original experiment included a surprise memory test. The prompt responses and retrieval performance are not of interest in this study, and will not be discussed further [see Paige et al . (2017 a) for further treatment of this issue].…”
Section: Methodsmentioning
confidence: 99%
“…An Easterner may instead preferentially attend to contextual information, such as relationships amongst individuals in the group, or the depicted group’s location. These biases have been linked to corresponding differences in visual search ( Wang et al , 2012 ) and recognition memory performance [ Millar et al , 2013 ; see Paige et al , 2017a for a corresponding functional magnetic resonance imaging (fMRI) study].…”
Section: Cultural Specialization Of Visual Cortexmentioning
confidence: 99%